The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jopr.13594
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy comparison of 3D‐printed post and core using castable resin and castable wax resin

Abstract: The purpose of this research was to compare the accuracy of threedimensionally (3D) printed post and core fabricated with two different materials: reinforced wax and castable resin. Materials and methods:Fifteen extracted single root central incisors were selected. Root canal treatment and tooth preparation for crown were performed on all teeth. Eleven millimeters post space was created with standardized prefabricated fiber post drill. Polyvinylsiloxane impression material was used for root canal impressions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…The same authors also compared the accuracy of reinforced printed wax and castable resin and found that both showed a volume reduction from the original file. 68 Three in vitro studies compared the accuracy of 3D-printed composite resin fixed single prostheses, such as crowns or inlays, to milled ones. Two studies showed superior overall fit and marginal fit for DLP 3D-printed crowns 69 and inlays, 70 respectively.…”
Section: Definitive Restorationsmentioning
confidence: 99%
“…The same authors also compared the accuracy of reinforced printed wax and castable resin and found that both showed a volume reduction from the original file. 68 Three in vitro studies compared the accuracy of 3D-printed composite resin fixed single prostheses, such as crowns or inlays, to milled ones. Two studies showed superior overall fit and marginal fit for DLP 3D-printed crowns 69 and inlays, 70 respectively.…”
Section: Definitive Restorationsmentioning
confidence: 99%
“…restoration boundaries, often leading to inadequate tooth structure reinforcement. 8 Furthermore, prefabricated fiber posts present clinical limitations, including bonding failures and adaptation challenges, 9 especially in elliptical root canals. 10 The gap between the dentin and these posts can result in an uneven resin cement layer, causing increased polymerization shrinkage, stress, and eventual post failure.…”
mentioning
confidence: 99%
“…10 The gap between the dentin and these posts can result in an uneven resin cement layer, causing increased polymerization shrinkage, stress, and eventual post failure. 6,9,10 The dearth of comprehensive data pertaining to the optimal material and dimensions for post cores has prompted scholarly investigation into novel materials within this domain. According to existing literature, custom-cast posts and cores have been found to exhibit enhanced adaptation in comparison to prefabricated posts.…”
mentioning
confidence: 99%
“…6 Using new technologies and materials to fabricate customized post and core has been evaluated in the literature. [7][8][9][10][11][12][13][14] Computer-aided design and computer-aided manufacturing (CAD-CAM) subtractive and additive manufacturing (AM) can be used to manufacture custom post and cores. 15 Subtractive methods cause waste of raw materials and require sustainability and precision of milling tools.…”
mentioning
confidence: 99%
“…Using new technologies and materials to fabricate customized post and core has been evaluated in the literature 7‐14 . Computer‐aided design and computer‐aided manufacturing (CAD‐CAM) subtractive and additive manufacturing (AM) can be used to manufacture custom post and cores 15 .…”
mentioning
confidence: 99%